2013
DOI: 10.5152/dir.2013.12021
|View full text |Cite
|
Sign up to set email alerts
|

Non-small cell lung cancer after surgery and chemoradiotherapy: follow-up and response assessment

Abstract: The imaging techniques in patients treated for lung cancer may be challenging to interpret. Radiologists are often asked to evaluate computed tomography (CT) scans after surgery, and this interpretation requires an understanding of both the timing and type of the surgical procedure. However, follow-up strategies are still not well defined. The assessment of tumor response to chemoradiotherapy relies on a tight integration of CT and clinical findings. Positron emission tomography-computed tomography (PET-CT) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
6
0
2
Order By: Relevance
“…However, their efficacies are compromised by development of resistance mechanisms (namely clonal evolution), which inevitably emerge in all patients with a median progression-free survival (PFS) ranging from a few months to a year (5)(6)(7). Response assessment primarily relies on imaging modalities, which may not reflect clonal evolution at molecular level (8). Therefore, there is a compelling need to develop improved modalities for monitoring clonal evolution.…”
Section: Introductionmentioning
confidence: 99%
“…However, their efficacies are compromised by development of resistance mechanisms (namely clonal evolution), which inevitably emerge in all patients with a median progression-free survival (PFS) ranging from a few months to a year (5)(6)(7). Response assessment primarily relies on imaging modalities, which may not reflect clonal evolution at molecular level (8). Therefore, there is a compelling need to develop improved modalities for monitoring clonal evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies showed that follow-up 18 F-FDG PET/CT scanning was valuable when conventional imaging results were equivocal for tumor recurrence (26)(27)(28). Moreover, our results showed that follow-up 18 F-FDG PET/CT scans with other different indications, including prior clinical suspicion of tumor recurrence, prior rising tumor marker or abnormal laboratory tests suggesting recurrence, prior rising tumor markers or abnormal laboratory tests, therapy response assessment of recurrence, intratherapy assessment of recurrence, and follow-up scanning to assess the previous equivocal response, led to a change in the management of patients in 20%-40% of scan times.…”
Section: Discussionmentioning
confidence: 99%
“…Setiap penyakit metastatik secara otomatis termasuk penyakit stadium IV dan biasanya tidak dapat dioperasi. 1,12,14 Penilaian obyektif pada perubahan tumor adalah penting untuk evaluasi respon tumor terhadap terapi, yang digunakan sebagai panduan saat ini adalah RECIST versi 1.1. Fitur utama meliputi ukuran minimum lesi terukur, lesi tidak terukur, lesi target, berapa banyak lesi yang diikuti, dan pengukuran satu dimensi untuk evaluasi keseluruhan beban tumor.…”
Section: 412unclassified